C++ for Dummies 5th Edition - Davis, Stephen Randy (Wiley Publishing, 2011)
If you’ve thought of programmers as elite intelligentsia who possess expertise (and perhaps genes) the rest of us will never have, think again. C++ For Dummies, 5th Edition, debunks the myths, blasts the barriers, shares the secrets, and gets you started. In fact, by the end of Chapter 1, you’ll be able to create a C++ program. OK, it won’t be newest, flashiest video game, but it might be a practical, customized inventory control or record-keeping program.